A photostable AIE fluorogen for lysosome-targetable imaging of living cells. Issue 32 (27th July 2016) - Lou, Xiaoding; Zhang, Mengshi; Zhao, Zujin; Min, Xuehong; Hakeem, Abdul; Huang, Fujian; Gao, Pengcheng; Xia, Fan; Tang, Ben Zhong
Abstract : We designed and synthesized a lysosome-targetable fluorescence probe, TPE-CA, which can sensitively and selectively monitor a subcellular organelle pH change. Abstract : Disruptive variation in intracellular pH and its fluctuations in lysosomes have a close relationship with the more acidic lysosome lumen of cancer cells (pH 4.5–5.5). Traditional lysosome-targeted probes, such as LysoTracker Green DND-26 (LTG) and LysoTracker Red DND-99 (LTR), can fluoresce when the weak base units in the probes are removed after donating protons under the photoinduced electron-transfer (PET) effect. However they can only be used at low concentration to avoid the aggregation-caused quenching (ACQ) effect and are also easily photobleached under continuous excitation irradiation, displaying low photostability. Herein, a tetraphenylethylene (TPE)-based lysosome-targetable fluorescence probe, TPE-CA, was synthesized, which could selectively monitor the pH change in subcellular organelles and exhibited a strong blue emission under an acidic condition with pH = 4. Using crystallographic, NMR and HRMS analyses, the mechanism regarding the pH dependent fluorescent performance of TPE-CA has been illustrated at the molecular level. In addition, experimental results show that TPE-CA is cell-permeable and biocompatible with HeLa, MCF-7 and HLF cells. The punctate fluorescent spots in the co-staining experiment of TPE-CA with LTG and LTR proves that the blue fluorescence spots of TPE-CA are indeed localized in the most acidic lysosome organelles. In particular, TPE-CA also inherits the aggregation-induced emission (AIE) feature of TPE, showing better photostability under continuous UV illumination compared with the commercial dyes (LTG and LTR). These results show that TPE-CA would be beneficial for understanding the acid environment of lysosomes in related cells and organs with potential biological significance.